The Importance of University Students’ Needs Identification to Support an Effective Communication Process in Teaching and Learning Activity - Fida Nirmala Nugraha (Faculty of Psychology, Universitas Surabaya, 2014)
Teaching is a form of effective communication between lecturer and his/her students allowing optimal transfer of learning. Failing to fulfill this would results in student passive or very submissive learning behavior. Effective instructional communication could be reached by identifying the students’ needs so lecturers can find the most appropriate teaching methods to fulfill the needs. Dominance, Influence, Steadiness, Conscientiousness/ Compliance (DISC) (Rosenberg & Silvert, 2013) inventory is a tool that can be used to identify the needs of the students. This preliminary study was keen to identify the needs of Telkom University Engineering Students from all majors in classroom communication. Results obtained through cross-tabulation analysis of DISC data from 6439 convenience samples (2009-2012 fresh students) reveal the basic academic needs: need to see how the content relates to their lives and pursue some interests of their own, and interpersonal/ instructional needs: inclusion and affection. Kegiatan mengajar merupakan salah satu bentuk komunikasi efektif antara dosen dan mahasiswanya sehingga terjadi transfer of learning yang optimal. Jika kebutuhan ini tak terpenuhi maka yang terjadi antara lain adalah perilaku belajar yang pasif/sangat pasrah, kurang gairah mencari informasi lebih lanjut. Komunikasi yang efektif dapat dicapai melalui identifikasi kebutuhan mahasiswa dalam berkomunikasi dengan menggunakan Dominance, Influence, Steadiness, Conscientiousness/Compliance (DISC) (Rosenberg & Silvert, 2013) inventory Penelitian ini merupakan survei pendahuluan untuk mengidentifikasi kebutuhan mahasiswa baru Fakultas Teknik Universitas Telkom 2009-2012. Dengan teknik non- probability sampling terutama convenience samples, 6439 data DISC diolah menggunakan analisis tabulasi-silang. Hasil menunjukkan bahwa kebutuhan mahasiswa baru 2009-2012 yang harus dipenuhi yaitu kebutuhan akademik dasar: kebutuhan untuk mengetahui keterkaitan antara pengalaman mereka dan materi pelajaran yang dipelajari; adapun kebutuhan interpersonal atau instruksional yang harus dipenuhi adalah kebutuhan untuk menjadi bagian dari kelompok, serta kebutuhan untuk diterima lingkungan.